Skala Kesesuaian Sistem pada Guru di Sekolah Inklusif untuk Mengukur Pengalaman Pengguna Aplikasi Pembelajaran SIBIKU - Hikmawati Nurul Insani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The purpose of this study is to evaluate the differences in scores among teachers in inclusive schools who use the SIBIKU sign language learning application by employing two instruments, the User Experience Questionnaire and the System Usability Scale. After using the application during instructional activities, teachers completed the questionnaires, and the collected data were analyzed descriptively and compared to identify variations across responses. The results show that the System Usability Scale primarily assesses ease of use, whereas the User Experience Questionnaire emphasizes satisfaction and innovative aspects. Furthermore, the findings provide a methodological foundation for User Experience research in inclusive education and offer initial evidence of the validity and reliability of both instruments within the Indonesian context. The low scores in the novelty and stimulation dimensions indicate that teachers require stronger pedagogical support, greater customization options, and enhanced interactive features to ensure better integration of the application into teaching practices. To clarify the distinction between design-related issues and measurement limitations, future research is recommended to employ longitudinal or intervention-based approaches and incorporate qualitative methods such as interviews and classroom observations.